EKSTRAK BUAH BAKAU Rhizophora mucronata Lamk SEBAGAI PEWARNA ALAMI PADA KAIN KATUN - Tasya Nabilla Septiandini; . Muflihati (Tengkawang : Jurnal Ilmu Kehutanan, 2019)
The fruit of Rhizophora mucronata Lamk content of tannin which can be used as natural dye color. Research purposes was to extract the fruit of R. mucronata, used the extract with fixation material as cotton natural dye, and evaluation the resistance of the color. The research was conducted for three months at Wood Technology laboratory and Wood workshop laboratory at Forestry Faculty Tanjungpura University. The fruit of R. mucronata was extraction with aquades with ratio 1:10 (weight/volume) at temperature ±80ºC for 60 minutes. The fixation materials were tawas, kapur tohor and tunjung. The cotton was dipped into the extract then analyzes the change of the color before and after the coloring process. After that the cotton was dipped into the fixation materials. The ratio of fixation materials and aquades was 1:20 (weight/volume). After coloring the change of the color was measured. Evaluation the resistance of the color after fixation was made refer on ASTM D 870-02-2002 for hot water treatment and ASTM D-1308-02-2013 for cold water treatment. The quality of color was measured with Munsell Soil Color Chart and Hunter Lab. The result of research showed that extract of R. mucronata give a pink color to the cotton with average value of ∆E was 22.74. The retention of extract to cotton was 4.47 g/cm3. The additional of fixation materials, i.e. tunjung and kapur tohor resulted the drak color meanwhile tawas made the lightest color. The average ∆E values were 6.16-39.84. Extract of fruit of R. mucronata with additional of tunjung as fixation materials can be used for natural dye for cotton and wood. Keywords : kapur tohor, natural dye, Rhizophora mucronata, tawas, tunjung